Ferromagnetic Enhancement in LaMnO3 Films with Release and Flexure. Issue 24 (17th November 2021) - Yao, Hongbao; Jin, Kuijuan; Yang, Zhen; Zhang, Qinghua; Ren, Wenning; Xu, Shuai; Yang, Mingwei; Gu, Lin; Guo, Er‐Jia; Ge, Chen; Wang, Can; Xu, Xiulai; et al.
Abstract: A variety of novel phenomena and functionalities emerge from lowering the dimensionality of materials and enriching the degrees of freedom in modulation. In this work, it is found that the saturation magnetization of LaMnO3 (LMO) films is largely enhanced by 56% after releasing from a brand‐new phase of tetragonal strontium aluminate buffer layer, and is significantly increased by 92% with bending films to a curvature of 1 mm −1 using a water‐assisted direct‐transferring method. Meanwhile, the Curie temperature of LMO films has been improved by 13 K. High‐resolution spherical aberration‐corrected scanning transmission electron microscopy and first‐principles calculations unambiguously demonstrate that the enhanced ferromagnetism is attributed to the strengthened Mn–O–Mn super‐exchange interactions from the augmented characteristics of the unconventional P 21 / n structure caused by the out‐of‐plane lattice shrinking after strain releasing and increased flexure degree of freestanding LMO films. This work paves a way to achieve large‐scale and crack‐and‐wrinkle‐free freestanding films of oxides with largely improved functionalities. Abstract : The saturation magnetization of LaMnO3 (LMO) films is enhanced by 56% after releasing from substrates, and is significantly increased by 92% with bending films to a curvature of 1 mm −1 . This enhancement of the ferromagnetism is attributed to the strengthened Mn–O–Mn super‐exchange interactions from the augmented characteristics of the unconventional P 21 / n structure of LMO films.